Food security strategies toward flood hazards along the Cinendang river, Aceh Province. Issue 1 (February 2021) - Bakhtiar; Abdullah, F; Marzuki, M; Yanis, M; Ismail, N
Abstract: Singkil communities have been living along riverbanks for several centuries. They are accustomed to living near the water which has generated local wisdom in mitigating and adapting to flood hazards. This study focuses on food security in overcoming flood hazards practiced as local wisdom by the community living along the Cinendang River, Aceh Singkil. The study applied a descriptive exploration based on field observations, interviews with local communities, and in-depth interviews with community leaders and local government regarding knowledge, experiences, and the implementation of the local wisdom. The result shows that the communities practice local wisdom on structural mitigation and adaptation so that they can still supply and protect their food needs during floods. The community has taken advantage of the floating buildings namely sapao metungkhang, lampung, and bagan for these purposes. These buildings are made of logs found drifting along the river, and they are practically effective in the way that daily household and communal activities can still be carried out in both normal conditions and during the flooding. Such houses are hardly found today due to shortages of raw materials, in-progress inland transportation development, relocation of communities far from rivers, and dimmed water caused by transportation routes.